Sei sulla pagina 1di 5
Ψ Ψ Ψ Ψ Ψ Ψ

Ψ

Ψ

Ψ

Ψ

Ψ

Ψ

2 dy 1 x + y − 1 = ; y(0) = 3 dx 2
2 dy 1 x + y − 1 = ; y(0) = 3 dx 2
2
dy
1 x + y − 1
=
;
y(0) = 3
dx
2
x + 2
x = u + h ∧ y = v + k u = x +
x = u + h
y = v + k
u = x + 2 v = y − 3
2
dy
1 x + y − 1
dv
1
v
=
⇐⇒
=
2 1 +
dx
2
x + 2
du
u 2
dv
v
1
=
⇐⇒
w + u dw
2 (1 + w) 2
uw = v
du
1
2 1
+ u 2
du =
u dw
1 + w 2
⇐⇒
=
du
2
1
⇐⇒
arctan(w) =
2 ln(u) + C
v
1
⇐⇒
arctan
=
2 ln(u) + C
u = x + 2 ∧ v = y − 3
y
y − 3
⇐⇒
arctan
1 2 ln(x + 2) + C
x
+
2 =
y(0) = 3
y
− 3
1
1
arctan
2 ln(x + 2) −
2 ln(2)
x
+ 2 =

3xy + cos(x) dx + 2x 2 + sin(x) dy = 0 x xy µ(x,
3xy + cos(x) dx + 2x 2 + sin(x) dy = 0 x xy µ(x,
3xy + cos(x)
dx + 2x 2 + sin(x) dy
= 0
x
xy
µ(x, y) = xf (y)
3x 2 y + cos(x) f (y)dx + 2x 3 + sin(x) f (y) dy
3x 2 y + cos(x) f (y)dx + 2x 3 + sin(x) f (y) dy = 0
y
∂N
− ∂M
∂x
∂y
dy
y 1 dy
M
f(y) = e
= e
= y
3x 2 y 2 + y cos(x) dx + 2x 3 y + sin(x) dy = 0
x 3 y 2 + y sin(x) =
C

( a ) ( b ) R 4 k p α 1 = (1 ,

(a)

(b)

R 4 k p α 1 = (1, 2, k, 1) α 2 = (k, 1, 2, 3) α 3 L.D.

W = (x 1 , x 2 , x 3 , x 4

 

x 1 x 3 + 2x 4

= 0

:

x 2 3x 3 + x 4

= 0

= (0, 1, p, 0)

R 4 R (2, 1, 0, 1) (1, 3, 1, 0)

(a) a(1, 2, k, 1) + b(k, 1, 2, 3) + c(0, 1, p, 0)
(a)
a(1, 2, k, 1) + b(k, 1, 2, 3) + c(0, 1, p, 0) = 0
a
+ bk
=
0
2a + b + c
ak + 2b + pc
=
0
=
0
a
+ 3b
=
0
1
k
0
|
0
1
k
0
|
0
2
1
1
|
0
 0
1 − 2k
1
|
0
 ∼
3 − k
0
k
2
p
|
0
2 − k 2
p
|
0
1
3
0
|
0
0
0
|
0
k = 3
 − 2k
1
k
0
|
0
1
3
0
|
0
1
0
1 1
|
0
0
1
|
0
− k 2
− 5
3 − k
 ∼
0
2 p
|
0
0
0
5p − 7
|
0
0
0
|
0
0
0
0
|
0
p = 7
5

      ( b ) W   ( x 1 , x 2 ,
   

 

(b) W

 

(x 1 , x 2 , x 3 , x 4 ) = a(2, 1, 0, 1) + b(1, 3, 1, 0) =

  x 1 = 2a + b

x 2 = a + 3b

x 3 = b

 

x 4 = a

 

W

= (x 1 , x 2 , x 3 , x 4

 

x 1 x 3 + 2x 4 x 2 3x 3 + x 4

= 0

= 0

:

x 1 x 3 + 2x 4

= (2a + b) (b) + 2(a) = 0 x 2 3x 3 + x 4

= (a + 3b) 3(b) + (a) = 0